Methoden und Techniken zur Integration von 122 GHz Antennen in miniaturisierte Radarsensoren - Beer, Stefan (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2013)
This thesis describes methods and techniques for realizing a fully integrated radar sensor in the frequency range above 100 GHz. The wavelength in the milimeter range leads to an antenna size in the range of a semiconductor die. This allows integrating antennas and a system-on-chip radar IC in a common chip package. Hence a fully integrated radio frequency system results within the chip package. This leads to a miniaturized, low-cost radar sensor for variuos applications.